Is There a Role for Vitamin D in Amyotrophic Lateral Sclerosis? A Systematic Review and Meta-Analysis - Lanznaster, Débora; Bejan-Angoulvant, Theodora; Gandía, Jorge; Blasco, Helene; Corcia, Philippe (Frontiers in Neurology, 2020)
Background: ALS is a neurodegenerative condition characterized by the progressive loss of motor neurons. Patients usually die 3 to 5 years after diagnosis from respiratory failure. Several studies regarding vitamin D investigated its role as a biomarker or a therapeutic option for ALS patients. In order to clarify the scientific evidence, we performed a systematic review and different meta-analyses regarding the potential role of vitamin D in ALS. Methods: we performed a systematic review of clinical trials, cohorts and case control studies retrieved from PubMed, EMBASE and Cochrane databases reporting vitamin D levels as a putative biomarker for ALS diagnosis or prognosis, or the effect of vitamin D supplementation in ALS patients. Whenever possible, data were pooled using a random effect model, with assessment of heterogeneity. Results: Out of 2996 articles retrieved, we finally included 13 research articles, 12 observational studies (50% prospective) and one clinical trial. We found that ALS patients had slightly lower levels of vitamin D than controls (mean difference -6 ng/ml, 95% CI [-10.8; -1.3]), but important confounding factors were not considered in the studies analyzed. We found no relation between vitamin D levels and ALSFRS-R, with highly heterogeneous results. Discordant results were reported in three studies regarding survival. Finally, five studies reported the effects of vitamin D supplementation with discordant results. Two of them showed a small improvement, while two others showed a deleterious effect on ALSFRS-R. One very small clinical trial with important methodological limitations showed some improvement in ALSFRS-R with high doses of vitamin D compared to normal doses. Conclusions: Our review did not find evidence to support a role of vitamin D on ALS diagnosis, prognosis or treatment. Most of studies had important limitations, mostly regarding the risk of bias for not considering confounding factors. Vitamin D supplementation should be offered to ALS patients to avoid other health issues related with vitamin D deficiency, but there is not enough evidence to support the use of vitamin D as a therapy for ALS.